Evaluation of Water‐Soluble Mannich Base Prodrugs of 2, 3, 4, 5‐Tetrahydroazepino[4, 3‐b]indol‐1(6H)‐one as Multitarget‐Directed Agents for Alzheimer's Disease. (4th December 2020) - Purgatorio, Rosa; de Candia, Modesto; Catto, Marco; Rullo, Mariagrazia; Pisani, Leonardo; Denora, Nunzio; Carrieri, Antonio; Nevskaya, Alisa A.; Voskressensky, Leonid G.; Altomare, Cosimo D.
Abstract: Different Mannich base derivatives have been studied with the aim of addressing the poor aqueous solubility of the recently disclosed 6‐phenethyl‐2, 3, 4, 5‐tetrahydroazepino[4, 3‐ b ]indol‐1(6 H )‐one (1 ), a human butyrylcholinesterase inhibitor (hBChE, IC50 13 nM) and protective agent in NMDA‐induced neurotoxicity, in in vivo assays. The N ‐(4‐methylpiperazin‐1‐yl)methyl derivative 2 c showed a 50‐fold increase in solubility in pH 7.4‐buffered solution, high stability in serum and (half‐life >24 h) and rapid (<3 min) conversion to 1 at acidic pH. Although less active than 1, 2 c retained moderate hBChE inhibition (IC50 =3.35 μM) and a significant protective effect against NMDA‐induced neurotoxicity at 0.1 μM. Moreover, 2 c resulted a weaker serum albumin binder than 1, could pass the blood–brain barrier, and exerted negligible cytotoxicity on HepG2 cells. These findings suggest that 2 c could be a water‐soluble prodrug candidate of 1 for oral administration or a slow‐release injectable derivative in in vivo Alzheimer's disease models. Abstract : To improve aqueous solubility for in vivo assay administration, Mannich base prodrugs of 6‐phenetyl‐2, 3, 4, 5‐tetrahydroazepino[4, 3‐ b ]indol‐1(6 H )‐one (1 ) were synthesized. Derivative 2 c had strongly improved solubility, and its pH‐dependent hydrolytic degradation to 1 (fast at gastric pH, slow at physiological pH) suggested 2 c as a possible prodrug for oral administration or slow‐release injection in in vivo AD models.